Historical trend of ozone-depleting substances and hydrofluorocarbon concentrations during 2004–2020 derived from satellite observations and estimates for global emissions. (1st January 2023) - Chen, Ao; Chen, Di; Hu, Xiaoyi; Harth, Christina M.; Young, Dickon; Mühle, Jens; Krummel, Paul B.; O'Doherty, Simon; Weiss, Ray F.; Prinn, Ronald G.; Fang, Xuekun
Abstract: Global concentrations (or mole fractions) and emissions of ozone-depleting substances (ODSs) and their hydrofluorocarbon (HFCs) substitutes that are controlled by the Montreal Protocol and its Amendments and adjustments (MP) are of great interest to both the scientific community and public. Previous studies on global concentrations and emissions have mostly relied on ground-based observations. Here, we assess the global concentrations and emissions of eight MP controlled substances and methyl chloride from ACE-FTS (Atmospheric Chemistry Experiment high−resolution infrared Fourier transform spectrometer) satellite observations: CFC-11 (CFCl3 ), CFC-12 (CF2 Cl2 ), CCl4, HCFC-22 (CHClF2 ), HCFC-141b (C2 H3 Cl2 F), HCFC-142b (C2 H3 ClF2 ), HFC-23 (CHF3 ), HFC-134a (C2 H2 F4 ), and CH3 Cl. Results show that the ACE-FTS satellite observations can be used to derive the concentrations and emissions of these ODSs, HFCs, and CH3 Cl, as they are consistent with those derived from the ground-based observations. Our findings imply that the changes in the concentrations and emissions of the ODSs and HFCs closely match the regulatory status of the MP, and satellite observations can be used to monitor the past and future progress of the MP. Graphical abstract: Image 1 Highlights: ACE-FTS satellite observations agree with ground-based observations. ACE-FTS satellite observations can be a supplement of ground-based observations. The trend of emissions of ODSs and HFCs closely matches the regulatory status of MP.